Recurrent ischemic stroke with patent foramen ovale linked to seronegative antiphospholipid syndrome: a case report and literature review - Zhou, Xin; Huang, Xiaoxiong; Zhou, Leliang; Zou, Yongbiao (Frontiers in Immunology, 2025)
The disability and mortality rates of recurrent ischemic stroke tend to be higher than those of the first stroke, which seriously affects the quality of life and prognosis of patients. Accurately identifying the etiology of stroke is critical for guiding effective treatment, and one of the most noteworthy in young patients is antiphospholipid syndrome (APS). Despite the progress made in APS research, seronegative APS (SN-APS) remains underdiagnosed. We present a case of recurrent ischemic stroke accompanied by PFO, which is associated with SN-APS. A 49-year-old female presented with expressive dysphasia and unresponsiveness on October 4, 2022. The magnetic resonance imaging (MRI) of cerebral revealed left frontal lobe infarcts; neither magnetic resonance angiography (MRA) nor magnetic resonance venography (MRV) showed significant hemodynamic stenosis or venous thrombosis. Subsequently, she was admitted to global aphasia and right hemiparesis and treated with intravenous thrombolysis and PFO closure on July 21, 2023. 9 months later, on April 23, 2024, she had a recurrence of ischemic stroke and tested negative for conventional antiphospholipid antibodies (aPL). However, the livedo reticularis on the inner side of the patient’s feet triggered our in-depth investigations and reflections. Due to the presence of positive non-criteria antibodies, the patient was eventually diagnosed with SN-APS and received standardized antithrombotic therapy. Our report suggests stroke can be a major manifestation of SN-APS, and a comprehensive evaluation by rheumatology and neurology teams is crucial to recognize it early. Prompt diagnosis and early anticoagulation therapy are beneficial to the prognosis of patients.